Effects of flooding on mental health: a case-control study - Pena-Andreu, José Miguel; Gil Aguilar, Virginia; Lucas Borja, Pilar; Lucas Borja, Manuel; Molero Carrasco, Julián; Fontalba-Navas, Andrés (My University, 2013)
﻿Background: Post-disaster mental health problems may affect population in different ways. Population exposure to a natural disaster has been associated with psychological distress, in particular, in the development of Posttraumatic Stress Disorder (PTSD). Most people experience distress after their exposure to an extreme event. For people with good psychosocial resilience and access to social support, mental health problems can be relatively less important since supporting relationships and inner capabilities may begin the adaptation processes. Mental disorders occur often, but less commonly than dis-tress, and in some cases they may require intensive and long term continuing interventions and treatment.
3rd International Congress on Neurobiology, Psychopharmacology & Treatment guidance (May 30th - June 2nd, 2013)
Keywords: Estrés (Psicología); Salud mental; Mental Health; Flooding; Case-control